Reduced Time to Positive Cutibacterium acnes Culture Utilizing a Novel Incubation Technique: A Retrospective Cohort Study. (April 2019) - Bokshan, Steven L; Ramirez Gomez, Jose; Chapin, Kimberle C; Green, Andrew; Paxton, E Scott
Introduction: Cutibacterium acnes ( C. acnes ) is a common pathogen in postoperative shoulder infections. The purpose of this study was to evaluate the time to positive cultures for C. acnes and compare our experience before and after implementation of a regulated anaerobic chamber system. We hypothesized that this would reduce the time to identify positive cultures. Methods: This was a retrospective review of 34 patients with cultures obtained from the shoulder that were positive for C. acnes . The time until positive result was evaluated before and after implementation of a regulated anaerobic incubation chamber. Results: Following implementation of the regulated anaerobic incubation chamber, the time until C. acnes culture growth significantly decreased from 6.5 days (range 3–10 days) to 4.9 days (range 2.75–10 days) (mean difference: 1.6 days, 95% confidence interval: 1.06–2.66 days; P = .002). True infections had a significantly shorter time to positive culture compared to contaminants (5.5 vs 6.8 days, respectively, P = .003). Increased number of positive culture specimens correlated with a shorter time to positivity (Spearman rank = −0.58, P = .007). Conclusion: Improved anaerobic culture protocols and techniques may lead to greater accuracy and earlier diagnosis and initiation of treatment of postoperative shoulder infections.